PROSES PERALIHAN HAK HARTA ASAL MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Andayani, Lily; Dwiprigitaningtias, Indah; Slamet, Sherly M.Imam (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
The legal institution of marriage is a legitimate bond between individuals who meet established legal criteria, designed to last indefinitely. Within this framework, the legal status of matrimonial property is crucial, as it determines the specific rights held by each spouse. A marital relationship can end, either through the death of one spouse (dissolution of marriage by death) or through an official divorce decree. Legally, a consequence of entering this bond is the formation of joint property. Nevertheless, Law Number 1 of 1974 concerning Marriage explicitly distinguishes between joint property and separate property (harta asal or personal property). The precise classification of this separate property often presents significant challenges, particularly during the process of property transfer, which potentially results in difficulties or losses for third parties. This research analyzes the process of transferring rights over separate property following the dissolution of marriage based on Law No. 1 of 1974 and identifies its legal implications. The main focus is on the legal mechanism to protect the rights of third parties in transactions involving separate property that has not been clearly classified.